External validation of the biomarker based ABCD score in atrial fibrillation patients with a non gender CHA2DS2 VASc score 0 to 1, A Korean multicenter retrospective cohort. (3rd October 2022) - Shin, S Y; Jung, M; Byeon, K; Kang, K; Park, Y; Hwang, Y; Lee, S; Jin, E; Roh, S; Kim, J; Ahn, J; Lee, S; et al.
Abstract: Background: Patients with low to intermediate risk atrial fibrillation (AF), defined as non-gender CHA2DS2-VASc score of 0–1, are still at risk of stroke. This study verified the usefulness of ABCD score (Age [≥60 years], B-type natriuretic peptide [BNP] or N-terminal pro-BNP [≥300 pg/ml], Creatinine clearance [<50 ml/min/1.73 m 2 ], and Dimension of the left atrium [≥45 mm]) for stroke risk stratification in non-gender CHA2DS2-VASc score 0–1. Methods: This multi-center cohort study retrospectively analyzed AF patients with non-gender CHA2DS2-VASc score 0–1. The primary endpoint was the incidence of stroke with or without anti-thrombotic treatment (ATT). An ABCD score was also validated. Results: Overall, 2694 patients (56.3±9.5 years; female, 726 [26.9%]) were followed-up for 4.0±2.8 years. The overall stroke rate was 0.84/100 person-years (P-Y), stratified as follows: 0.46/100P-Y for an ABCD score 0; 1.02/100P-Y for an ABCD score≥1. The ABCD score was superior to the non-gender CHA2DS2-VASc score in stroke risk stratification (C-index=0.618, P=0.015; net reclassification improvement=0.576, P=0.040; integrated differential improvement=0.033, P=0.066). ATT was prescribed in 2353 patients (86.5%), and the stroke rate was significantly lower in patients receiving non-vitamin K antagonist oral anticoagulant (NOAC) therapy and an ABCD score≥1 than in those without ATT (0.44/100P-Y versus 1.55/100 P-Y; hazard ratio=0.26, 95% confidence interval 0.11–0.63, P=0.003). Conclusion: The biomarker-based ABCD score demonstrated improved stroke risk stratification in AF patients with non-gender CHA2DS2-VASc score 0–1. Furthermore, NOAC with an ABCD score≥1 was associated with significantly lower stroke rate in AF patients with a non-gender CHA2DS2-VASc score 0–1. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Korean Disease Control and Prevention Agency